Spaces for stardom urban spatial practice and the feminization of Flânerie in the SMDC advertising campaign - Sarmiento, Maria Alicia A. (2013)
This paper explores spatial practice and social ordering in the advertising campaign of the SM Development Corporation (SMDC)?the country?s largest real estate developer. Through print, outdoor, and video materials, viewers are invited to ?Live like a star!? in any of SMDC?s 16 high-rise condominiums. In framing images of the built environment, celebrity endorsers, and luxury retail and tourism, the corporation creates a heterotopia, or a juxtaposition of otherwise incompatible images, that simultaneously represents and influences the social order. For the purposes of this paper, the researcher has chosen to focus on the heterotopia created at the intersection of the built environment and the images projected through the SMDC billboards. Using this heterotopia, SMDC exploits reconfigurations of the domestic sphere within the new economy, and the shifting role women play within it. Both star and sanctum are composed into a utopian prescription, projecting how architecture, the entertainment sector, and the advertising industry come together to construct a global future in the framework of celebrity and abstract space, built on the unstable foundations of institutionalized dispossession and separate development.